Electrochemical Synthesis of Nanocrystalline Ni0.5Zn0.5Fe2O4 Thin Film from Aqueous Sulfate Bath. (10th May 2012) - Saba, A.; Elsayed, E.; Moharam, M.; Rashad, M. M.
Abstract : Nanocrystalline nickel-zinc ferrites Ni0.5 Zn0.5 Fe2 O4 thin films have been synthesized via the electrodeposition-anodization from the aqueous sulfate bath. The electrodeposited (Ni-Zn)Fe2 alloy was anodized in aqueous 1 M KOH solution to form the corresponding hydroxides which annealed at different temperatures ranging from 800 to 1000 ∘ C for various periods from 1 to 4 h, to get the required ferrite. SEM micrograph of the formed ferrite particles, annealed at 1000 ∘ C for 4 h appeared as the octahedral-like structure. A good saturation magnetization of 28.2 emu/g was achieved for Ni0.5 Zn0.5 Fe2 O4 thin film produced after the aforementioned conditions. The kinetic studies of the crystallization of Ni0.5 Zn0.5 Fe2 O4 films appeared to be first-order reaction and the activation energy was found to be 10.5 k Joule/mole.